Tweets of surveillance: Traffic, Twitter, and securitization in Beirut, Lebanon. (September 2017) - Monroe, Kristin V.
More than a decade ago, Akhil Gupta and James Ferguson set out to define a research program with their essay 'Spatializing States: Toward an Ethnography of Neoliberal Governmentality' (2002). Exploring the relation between what they referred to as 'the spatial and statist orders, ' they argued that conceptualizations of the nature of the state have not attended adequately to the ways in which states are spatialized and endeavored to show, through ethnography, how people come to experience the state as an entity with certain spatial characteristics and properties. Building on these ideas, but also moving beyond their taken-for-granted assumptions about the state's spatiality, this essay makes use of one ethnographic case example in an effort to offer a fine-grained illustration of the spatial dimensions of the project of state securitization in the urban landscape. I do this by looking closely at the field of urban mobility in Beirut, Lebanon, and the Twitter account for the city's Traffic Management Center, launched in late 2013 by the Ministry of Interior. Through my analysis of the spatial modes of statecraft that are produced through this Twitter account, I develop an argument about how the social media technology of Twitter serves as a portal through which to view how the state secures its legitimacy and naturalizes its authority in both virtual and physical space, while, at the same time, this technology – if only fleetingly – can be harnessed to issue challenges to this legitimacy and authority. What is at stake in the Traffic Management Center's Twitter account, I suggest, is the production of the state as an entity that is not just powerful in the sense of being vertical to society and encompassing of urban space, but the very idea that the state offers security and protection to its citizens.